INVESTIGATION OF THE EFFECT OF WINDOW SHADES TYPE ON THE OTTV IN U COLLEGE BUILDING OF BANDUNG STATE POLYTECHNIC - Akmal, Muhammad; Kurniasetiawati, Annisa Syafitri (Politeknik Negeri Sriwijaya, Indonesia, 2023)
The U building is the college building for the Department of Refrigeration and Air Conditioning, Bandung State Polytechnic. However, during the afternoon teaching, the third floor is often complained of feeling hot and disrupting the teaching and learning process. This is caused by the size of the window on the third floor is too large and does not use any shade. This research was conducted to determine the OTTV value of the existing U Building and then investigate the potential for improving the OTTV value by changing window glass materials or adding shading such as window film. This study used primary and secondary data collection methods. The primary data consisted of: building dimensions, glass dimensions, door dimensions, ambient temperature, inside temperature, wall and glass surface temperatures, and glass types. Meanwhile, some secondary data, namely building U as built drawings, wall specifications, and glass specifications used. It was found that the existing OTTV value of the Lecture U Building reached 39.78 W/m2 where this value was above the SNI 03-6389 2011 standard. By investigating the installation of shading such as window film and double glass it was possible to minimize the building's OTTV value to 36.78 W/m2 for window film and 33.86 W/m2 for the addition of double glass accompanied by window film.